Reusability techniques in load-flow analysis computer program - Nor, K.M.; Mokhlis, Hazlie; Gani, T.A. (Institute of Electrical and Electronics Engineers (IEEE), 2004)
This paper describes the implementation of reusability aspects in producing load-flow analysis software application. The reusability in the algorithm and codes are obtained by applying matrix partitioning approach for Newton method and sequential approach for Fast Decoupled method. The software is built by using component-based development and object oriented programming methodologies. These methodologies made the developed load-flow analysis software flexible for future enhancement. Adding and changing codes and algorithm of the software can be done without affecting much the existing codes and algorithms. By maximizing the reusability aspects, the cost and time of software maintenance for updating can be reduced.